2017
DOI: 10.1177/0886260517738780
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and Violence Against Women in Rural Guatemala

Abstract: Violence against Women (VaW) has come to be recognized as a serious human rights abuse with important consequences not only for women but for whole societies. Since VaW has several manifestations, it is possible to differentiate among different types of violence. In this article, a broad theoretical framework with different dimensions of gender violence was adapted to a Latin American social and cultural context to measure three out of the five main types of violence: economic violence, emotional psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
8
0
3
Order By: Relevance
“…The literature on the repercussions of MP on levels of psychological violence against women remains scarce, precluding any conclusion. There are only two studies evaluating this relationship 13,40 . Compared to research on physical abuse, the small number of studies focusing on psychological violence emphasizes the need to expand the debate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the repercussions of MP on levels of psychological violence against women remains scarce, precluding any conclusion. There are only two studies evaluating this relationship 13,40 . Compared to research on physical abuse, the small number of studies focusing on psychological violence emphasizes the need to expand the debate.…”
Section: Resultsmentioning
confidence: 99%
“…Only two surveys assessed the repercussions of MP following psychological violence. One found a protective effect 40 , whereas the other suggested that women attending the program five or more years tended to experience less victimization 13 . Two studies examined the relationships between MP and sexual violence.…”
Section: • Microcredit Programsmentioning
confidence: 97%
“…Our main motive in the present paper was to reiterate the impact of microfinance on spousal violence in India vis-a-vis to look into the potential determinants of spousal violence. While on one hand, studies indicate a reduction of spousal violence due to credit program participation (Cepeda et al, 2017; Kapiga et al, 2019; Nawaz, 2015), on the other hand, few supports the opposite notion (Bajracharya & Amin, 2013; Dalal et al, 2013). Though largely our bivariate and multivariate result conforms with the latter proposition that microfinance participants are more likely to experience spousal violence, the results of our GIS analysis reveal that credit program participation reduces violence (although for a few states only).…”
Section: Discussionmentioning
confidence: 99%
“…However, by analyzing the panel data of Rojiroti, a small organization that runs microfinance programs for the weakest section of women in Bihar, India, Gordon 2016 concludes that microfinance results in the reduction of domestic violence. Similarly, studies based on South Africa (Kim et al, 2007;Pronyk et al, 2006), rural Guatemala (Cepeda et al, 2017), and Tanzania (Kapiga et al, 2019) show that microfinance based intervention reduce IPV.…”
Section: Microfinance and Intimate Partner Violencementioning
confidence: 93%
“…Previous empirical research has studied this type of violence through analysis at the micro level. Individual women were asked about their opportunities to make free decisions on family planning, education, health, clothes to wear, leaving home, travel, speaking with other men, or visiting friends (Cepeda et al, 2021; Panda, 2014; among many others). There is also research at the macro level, using indicators such as “Percentage of women having experienced psychological violence” (EIGE, 2020a); “Marital control,” “Freedom of movement” or “Obligation to obey their husbands” (Krug et al, 2002, p. 95); “Laws relating to gender inequality” (Krug et al, 2002, p. 161); and “Coercion suffered by women to freely make decisions regarding the family planning” (Bloom & Gates, 2015).…”
Section: Theoretical Framework and Related Literaturementioning
confidence: 99%